2022
DOI: 10.26434/chemrxiv-2022-3smb7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monkeypox Virus Aggressively Invades via GP120 Domains and PI3K/GTPase-like System of F13 Protein

Abstract: Infection with the monkeypox virus (MPXV) causes a condition comparable to that of smallpox, albeit with fewer symptoms and severity. The typical magnitude and duration of monkeypox epidemics will increase as human protection from the smallpox vaccine wanes. In this study, the bioinformatics technique of domain search was utilized to investigate the biological function of the F13 protein of the E protein of the monkeypox virus. According to the research annotation results, the F13 protein has G120, EF-hand, Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A bioinformatic study has suggested that MPXV could bind to cellular receptors in a way similar to VACV MV and HIV, using PI3K/Akt and GTPase signaling pathways to promote its internalization into host cells [61].…”
Section: Lipid Rafts and Vacv Infectionmentioning
confidence: 99%
“…A bioinformatic study has suggested that MPXV could bind to cellular receptors in a way similar to VACV MV and HIV, using PI3K/Akt and GTPase signaling pathways to promote its internalization into host cells [61].…”
Section: Lipid Rafts and Vacv Infectionmentioning
confidence: 99%